Relationship between carotid atherosclerosis and lipoprotein (a) in patients with acute ischemic stroke - Zhao, Yongna; Wang, Zhichao; Ji, Ruijun; Wang, Yongjun; Zhang, Yaguang; Yu, Kai (Frontiers in Neurology, 2024)
Objective This study aimed to examine the relationship between lipoprotein (a) (Lp[a]) and other blood lipid indexes and carotid artery atherosclerosis in patients with acute ischemic stroke (AIS). Methods A total of 2,018 patients were selected from the hospital “acute stroke intervention and secondary prevention registration database” by identifying blood fat indexes (cholesterol, triglyceride, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol and Lp[a]). Based on the results of carotid artery ultrasound examinations, the patients were divided into a “no plaque” group, comprising 400 patients, a “plaque and no stenosis” group, comprising 1,122 patients and a “carotid stenosis” group, comprising 496 patients. The relationship between Lp(a) and blood lipid indexes and carotid artery atherosclerosis was then investigated using multi-factor logistics regression analysis. Results There were 400 patients (19.8%) with no carotid plaque, 1,122 patients (55.6%) with plaque and no carotid stenosis and 496 patients (24.6%) with carotid stenosis. As the degree of carotid artery atherosclerosis increased, the Lp(a) level gradually increased; Lp(a) and cholesterol were identified as independent risk factors for carotid atherosclerosis. Conclusion Lipoprotein (a) and cholesterol are independent risk factors for patients with AIS with carotid atherosclerosis, and their levels increase with the degree of carotid artery atherosclerosis; therefore, attention should focus on levels of cholesterol and Lp(a) in acute stroke patients to control atherosclerosis effectively.